Government Strategy in Stabilizing Post-Harvest Agricultural Product Prices in Bima Regency - Pane, Armin; Rahman, Abdul; Wahyudi, Sigit (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze government strategies in stabilizing post-harvest agricultural commodity prices in Bima Regency. A qualitative approach with a descriptive-analytical method was used. Data were collected through in-depth interviews, field observations, document studies, and SWOT analysis. The findings indicate that price fluctuations of major commodities such as corn, shallots, and rice remain a serious issue for farmers. Government strategies like minimum support prices and subsidies have not been fully effective due to limited infrastructure, weak inter-agency coordination, and low farmer participation. Therefore, there is a need to strengthen farmer institutions, develop post-harvest infrastructure, and utilize digital technology in distribution and marketing systems. These findings offer strategic recommendations for policymakers to establish a more resilient and sustainable price stabilization system